Importance of early ventilation tubes insertion in chronic otitis media with effusion in children with congenital cleft palate - Šubarević, Vladan; Arsović, Nenad; Simić, Radoje; Stanković, Katarina (Vojnosanitetski pregled, 2020)
Background/Aim. Otitis media with effusion (OME) is almost universal in children with cleft palate with an incidence of more than 90%, but the approach to managing this problem varies significantly among authors. The Eustachian tube dysfunction is the main factor that leads to the presence of the middle ear effusion. This is especially prominent in children with congenital cleft palate and explains the prolonged course of this process. The objective of this study was to determine the effectiveness of early ventilation tubes insertion in children with cleft palate at the time of palatoplasty by monitoring the course and duration of the disease as well as development of complications.  Methods. In the prospective study with predefined regular follow-up intervals and parameters, the two groups of children were observed. The group one (E) included 45 children with congenital cleft palate who underwent the early insertion of ventilation tubes during palatoplasty, and the group two (C) had the same number of children with cleft palate who were treated conservatively on an as-needed basis. Assessment parameters were findings of otomicroscopy, tympanometry, play and pure tone audiometry. Each child was followed-up for 5 full years at total of nine follow-up examinations.  Results. Result analysis showed that there were no statistically important differences between the two study groups in terms of the course and duration of the presence of the middle ear effusion, or in terms of complications and speech development. Conclusion. Based on the results obtained, we can conclude that there is no significant benefit in early ventilation tubes insertion in children with cleft palate, therefore our recommendation is watchful waiting and a conservative treatment on an as-needed basis, with the ventilation tubes insertion when a surgeon, based on his or her experience and individual findings considers it necessary.
Keywords: otitis media with effusion; cleft palate; middle ear ventilation; conservative tretment; otologic surgical procedures; child; serbia